2016
DOI: 10.1016/j.cbpa.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Halloween genes in ecdysteroids biosynthesis of the swimming crab (Portunus trituberculatus): Implications from RNA interference and eyestalk ablation

Abstract: Molting, including metamorphosis molting in arthropods are controlled by the ecdysteroids that are synthesized and secreted by the crustacean Y-organ (YO) or the insect prothoracic gland (PG). The Halloween genes encoding the enzymes mainly involved in the biosynthesis of ecdysteroids are well studied in insects but not in crustaceans. Given the importance of Halloween genes in ecdysteroids biosynthesis, we have previously reported the cDNA cloning of disembodied (Dib) in P. trituberculatus. Here, cDNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Expression of these genes was observed in other tissues such as the EG, thoracic ganglia complex, brain, and ovary. A similar pattern has been observed in P. trituberculatus [26], but further study of the localization and translation of mRNAs in these tissues is needed. Neverland and Spook have been identified in ovarian cells in other species such as the salmon louse, Lepoeophtheirus salmonis [64], the water flea, D. magna [65], the acari, Ornithodoros moubata [66], the mosquito, Anopheles gambiae [67], and the fruit fly, Drosophila melanogaster [68].…”
Section: Plos Onesupporting
confidence: 64%
See 1 more Smart Citation
“…Expression of these genes was observed in other tissues such as the EG, thoracic ganglia complex, brain, and ovary. A similar pattern has been observed in P. trituberculatus [26], but further study of the localization and translation of mRNAs in these tissues is needed. Neverland and Spook have been identified in ovarian cells in other species such as the salmon louse, Lepoeophtheirus salmonis [64], the water flea, D. magna [65], the acari, Ornithodoros moubata [66], the mosquito, Anopheles gambiae [67], and the fruit fly, Drosophila melanogaster [68].…”
Section: Plos Onesupporting
confidence: 64%
“…Most Halloween genes are found among other arthropod species. For example, the water flea, Daphnia pulex has orthologs of all 5 of these genes [25] while four (cytochrome P450 (CYP), 307A1 (spook), CYP315A (shadow), and CYP306A1 (phantom)) are found in the swimming crab, Portunus terituberculatus [26] and the kuruma prawn, Marsupenaeus japonicus [6]. However, while spook and spookier have been detected in arthropods, potentially involved in the second step of the Ecd synthesis (transformation of 7-dehydrocholesterol (7dC) to Δ4-Diketol and Diketol), only a spook homolog has been identified in crustaceans [27].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, transcript levels of the spook gene, a class 1 monooxygenase involved in diketol synthesis from cholesterol, increased 25- to 35-fold relative to the other ecdysteroid pathway enzymes following entry into early premolt. qPCR studies in the swimming crab, Portunus trituberculatus , did not report an increase in spo transcripts on entering premolt 68 . In insects, however, a homolog of this gene, spookier , is subject to transcriptional up-regulation by the zinc finger transcription factor Ouija board ( ouib ), which is principally expressed in the ecdysteroidogenic prothoracic gland 69 , 70 .…”
Section: Discussionmentioning
confidence: 93%
“…They were called "Halloween Family Gene" and play significant role in the synthesis of ecdysone (Nusslein-Volhard, 1980). In crustaceans, Xie et al (2016) successfully cloned the disembodied (dib), spook (spo), and shadow (sad) genes from Portunus trituberculatus (Liu et al, 2015), and Chang and O'Connor (1977) found that the expression level of these genes in Y-organ was significantly higher than that of other tissues, which was consistent with the conclusion that the Y-organ is the primary secretory organ of crustacean synthetic ecdysone.…”
Section: Function Analysis Overview and Analysis Of Main Metabolic Pamentioning
confidence: 99%